Analysis of Communication Patterns between Leaders and Staff in the Protocol and Communication Section of the Leadership Secretariat of Seluma Regency - Chendi Eko Saputra; Sri Narti; Martha Heriniazwi (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze communication patterns between leaders and staff in the Protocol and Leadership Communication Division (Prokopim) of the Seluma Regency Regional Secretariat. Organizational communication is understood as a mechanism that regulates the flow of information and influences the effectiveness of bureaucratic work. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation of the Head of Division, Head of Subdivision, functional officials, and implementing staff. Based on Keith Davis's (1953) communication pattern theory (R. Wayne Pace & Don F. Faules (2010)), the results show that the communication pattern in Prokopim is adaptive. The Wheel and Chain patterns dominate hierarchical formal communication, while the Y-Pattern emerges in inter-agency coordination with the Subdivision Heads as liaisons. At the operational level, the Circle pattern is evident in horizontal discussions among staff, while the All-Channel pattern develops through the use of digital media such as WhatsApp. These findings indicate that the diversity of communication patterns supports smooth work, but there are still obstacles in the form of dependence on leaders, delays in information, and suboptimal management of digital communication. Therefore, delegation of authority, simplification of information channels, and strengthening of digital archives are needed to improve the effectiveness of organizational communication.